Identification of a Plasmodium falciparum inhibitor‐2 motif involved in the binding and regulation activity of protein phosphatase type 1. (8th September 2014) - Fréville, Aline; Tellier, Géraldine; Vandomme, Audrey; Pierrot, Christine; Vicogne, Jérôme; Cantrelle, François‐Xavier; Martoriati, Alain; Cailliau‐Maggio, Katia; Khalife, Jamal; Landrieu, Isabelle
<x xml:space="preserve">Abstract</x> The regulation of Plasmodium falciparum protein phosphatase type 1 (PfPP1) activity remains to be deciphered. Data from homologous eukaryotic type 1 protein phosphatases (PP1) suggest that several protein regulators should be involved in this essential process. One such regulator, named PfI2 based on its primary sequence homology with eukaryotic inhibitor 2 (I2), was recently shown to be able to interact with PfPP1 and to inhibit its phosphatase activity, mainly through the canonical 'RVxF' binding motif. The details of the structural and functional characteristics of this interaction are investigated here. Using NMR spectroscopy, a second site of interaction is suggested to reside between residues D94 and T117 and contains the 'FxxR/KxR/K' binding motif present in other I2 proteins. This site seems to play in concert/synergy with the 'RVxF' motif to bind PP1, because only mutations in both motifs were able to abolish this interaction completely. However, regarding the structure/function relationship, mutation of either the 'RVxF' or 'FxxR/KxR/K' motif is more drastic, because each mutation prevents the capacity of PfI2 to trigger germinal vesicle breakdown in microinjected Xenopus oocytes. This indicates that the tight association of the PfI2 regulator to PP1, mediated by a two‐site interaction, is necessary to exert its function. Based on these results, the use of a peptide derived from the 'FxxR/KxR/K' PfI2 motif was investigated for its potential effect on Plasmodium growth. This peptide, fused at its N‐terminus to a penetrating sequence, was shown to accumulate specifically in infected erythrocytes and to have an antiplasmodial effect. Structured digital abstract PfPP1 and PfI2 bind by nuclear magnetic resonance (1, 2) PP1 physically interacts with PfPP1 by anti tag coimmunoprecipitation (View interaction) PfI2 binds to PfPP1 by enzyme linked immunosorbent assay (View interaction) PfI2 binds to PfPP1 by surface plasmon resonance (1, 2, 3, 4)